The scriptural «invention» of the city. The discourse on space as a way of approaching social representations (Islas, 2024)
Introduction: The study of the social production of space is a fundamental key to understanding the formation of power structures and relations and to locate social subjects in line with the position occupied within said political chess.Methods: The methodological and theoretical approaches currently present in the historiographic field, the selection of analytical and theoretical tools that ranging from critical discourse analysis to linguistics and from urban cultural history, to urban semiotics or human geography.Results: Space becomes a story that imprisons and constructs the subjectivities and attitudes of the different social actors, it is an inseparable part of the territorial meanings and symbols as a whole, but at the same time it constitutes a generality that imposes its identity discourses on the linguistic community and territorial that challenges it.Conclusions: Spatial structures order, not only the representation of the world of the subjects, but the individual as such, who orders himself based on this representation. The discourse on territory stands as a resource to elaborate in an argumentative way the debate on physical space, its social determination and the class differences it generates in its appropriation.
Keywords: social space; territory; social representation; discourse